Católicos e relações de classe: as visões de Liga Operária Católica, Juventude Operária Católica e Associação Cristã de Empresários e Gestores - Costa, Joaquim (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2021)
This paper focuses on a theme that has been underestimated: that of reciprocal relations and representations between Catholics separated by different class belongings, in this case, between employers and workers. These representations focus on the relationship between labor and capital, as well as on the production and distribution / redistribution of wealth, and involve the notion of social justice. I chose to study, three Catholic associations - one of businesspersons (Associação Cristã de Empresários e Gestores / ACEGE – Association of Christian Entrepreneurs and Managers), one of workers (Liga Operária Católica / LOC – Catholic Worker's League), another of young people, mainly students, but of working-class tradition (Juventude Operária Católica / JOC – Young Catholic Workers) - based on their own documents and interviews. ACEGE members see religion as integrative and never insubordinate in the company; LOC members reveal a disenchanted conception of economic relations that forces permanent mobilization and an eventually disruptive role for religion; JOC lacks systematic opinion and reveals the generational limits it faces.